PENERAPAN KONSEP COMMUNITY BASED TOURISM PADA DESA WISATA BANYU MILI WONOSALAM JOMBANG - Dwi Ermayanti Susilo; Ina Nikmatul Chasanah (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
The development and growth of tourist villages spread to all provinces in Indonesia, one of which is East Java Province, especially in Jombang Regency. Tourism development aims to provide benefits for both tourists and the host community. With the development of tourism is expected to be able to improve the standard of living of the community through the economic benefits brought to the area. The Wonosalam Village and BUMDes are currently thinking about how to develop the Banyu mili Wonosalam Jombang Tourism Village which is still experiencing problems such as the lack of variety of tourism activities and tourism support facilities such as easy access to tourist sites and the unavailability of public transportation that can directly reach tourist sites. , this causes the low interest of tourists to visit.